Burgernomics: Raw BMI vs Adjusted BMI. A comparative analysis of appropriate exchange rate valuation measures - Gumedze, Siyanda Nakiwe Nomfundo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The Big Mac Index was developed in 1986 by The Economist magazine as a playful take on the Purchasing Power Parity theory. Its purpose is to indicate whether a currency is overpriced or undervalued in relation to the real exchange rate and whether it can be used as a reliable indicator of exchange rate predictions. There are two versions of the Big Mac Index: the raw Big Mac Index and the adjusted Big Mac Index. If appropriate, this index might be developed into an economic theory that can be applied to corporate finance, international trade, and international finance. To determine which Big Mac Index measure is a better indicator of exchange rate valuation, a comparison analysis was conducted. This study set out to determine how well the adjusted Big Mac Index performed as a gauge for exchange rate valuation. The research then compares the two Big Mac Index measures' ability to anticipate future exchange rates in order to determine which is more accurate. Data from the South African Reserve Bank and The Economist databases covering 37 nations from 2000 to 2022 were used for the analysis. Exchange rate misalignment trends were assessed globally, and the results indicated that the adjusted BMI was a more accurate measure of purchasing power. Tests of correlation revealed that there was a positive association between the real exchange rate and the Big Mac Index. Findings from a panel ARDL Model indicated that taking into consideration country-specific GDP variations and group heterogeneity can enhance the real exchange rates' ability to predict the raw BMI. The research also focused on the South African Rand to ascertain whether the Big Mac Index validates the Purchasing Power Parity theoretical framework. Using cointegration tests and graphic analysis, it was possible to find evidence for a cointegrating relationship between the real exchange rate and the Big Mac Index measures during the last 20 years. Additionally, a positive correlation between the modified Big Mac Index and terms of trade was discovered in the results, confirming the hypothesis that the Big Mac Index satisfies current account assumptions. Finally, a VEC model demonstrated that the modified BMI outperforms the raw BMI in terms of forecasting estimates. Overall, the study found that the Big Mac Index is more than a bit of fun as per its origin. The results showed that the adjusted Big Mac Index has practical applications and the potential to be considered as an economic theory.
Keywords: Big Mac Index; Purchasing power parity; Foreign exchange rates; Foreign exchange market; Economic theory